Utilization of home- and community-based services among rural family caregivers of persons with dementia: the role of the area deprivation index - Santoyo-Olsson, Jasmine; Covinsky, Kenneth E.; Cheng, Jing; Gallagher Thompson, Dolores; Yank, Veronica (Frontiers in Public Health, 2025)
BackgroundDementia significantly impacts rural communities in the U.S., presenting unique challenges for family caregivers due to limited access to essential support services. This study examines the influence of area-level factors on the utilization of home- and community-based services among rural caregivers.MethodsUsing Andersen’s extended behavioral model of health services utilization, baseline data (n = 361) from family caregivers participating in a national randomized trial evaluating the Building Better Caregivers workshop were analyzed. Participants completed an online survey assessing home- and community-based support services and caregiving aspects. Area-level factors were measured using the Area Deprivation Index (ADI) and U.S. Census region, linked to respondents ZIP+4 code and state. Multivariable logistic regression analyses assessed the relationship between area-level factors and support service utilization.ResultsAbout 65% of caregivers used at least one support service, with 52% utilizing home-based services and 52% community-based services. Caregivers in the most deprived rural areas were significantly less likely to use any support services (OR = 0.45; 95% CI [0.23, 0.89]) and community-based services (OR = 0.26; 95% CI [0.26, 0.86]) compared to those in the least deprived rural areas. No significant associations were found between Census region and any type of support service utilization.ConclusionService utilization differences within rural areas highlight the need for nuanced, area-specific interventions to enhance support service accessibility for caregivers in deprived rural areas, improving caregiving outcomes. Future research should further investigate area-level variations and their interactions with individual factors to better understand barriers faced by rural caregivers.Trial registrationhttps://clinicaltrials.gov/ct2/show/NCT04428112, identifier NCT04428112.